2019
DOI: 10.1136/emermed-2018-208305
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of the form and function of primary care services in or alongside emergency departments: concepts paper

Abstract: Primary care services in or alongside emergency departments look and function differently and are described using inconsistent terminology. Research to determine effectiveness of these models is hampered by outdated classification systems, limiting the opportunity for data synthesis to draw conclusions and inform decision-making and policy. We used findings from a literature review, a national survey of Type 1 emergency departments in England and Wales, staff interviews, other routine data sources and discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(69 citation statements)
references
References 6 publications
0
66
0
Order By: Relevance
“…Effectiveness will be evaluated by waiting times, admission rates and (re)attendances, patient satisfaction, and cost-consequence analysis, with patient safety incident reports analysed for patient safety outcomes. The teams have collaborated to update the taxonomy to ensure consistency of terminology and classification of models, and to include the wider primary care workforce 13Figure 2. shows the form these service models take, inside and outside emergency departments 13.…”
Section: Is Ongoing Research Likely To Provide Relevant Evidence?mentioning
confidence: 99%
See 3 more Smart Citations
“…Effectiveness will be evaluated by waiting times, admission rates and (re)attendances, patient satisfaction, and cost-consequence analysis, with patient safety incident reports analysed for patient safety outcomes. The teams have collaborated to update the taxonomy to ensure consistency of terminology and classification of models, and to include the wider primary care workforce 13Figure 2. shows the form these service models take, inside and outside emergency departments 13.…”
Section: Is Ongoing Research Likely To Provide Relevant Evidence?mentioning
confidence: 99%
“…The teams have collaborated to update the taxonomy to ensure consistency of terminology and classification of models, and to include the wider primary care workforce 13Figure 2. shows the form these service models take, inside and outside emergency departments 13. The studies, due to be completed in 2021, will attempt to identify service models that may be better suited depending on local demographics and contexts.…”
Section: Is Ongoing Research Likely To Provide Relevant Evidence?mentioning
confidence: 99%
See 2 more Smart Citations
“…A 2019 review found inconsistent terminology around primary care services in emergency departments, as numerous different models were put under the same umbrella. Any meaningful evaluation must be much clearer about defining the delivery model and not comparing apples and oranges 8…”
Section: The Evidencementioning
confidence: 99%